Determinants of Stunting in Toddlers Aged 24-59 Months in East Jambi District, Jambi City in 2025 - Kiki Ayu Apriani; Asparian Asparian; Herwansyah Herwansyah; Dwi Noerjoedianto; Muldiasman Muldiasman; Willia Novita Eka Rini (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Stunting is a chronic nutritional problem that remains a challenge in Indonesia, including in Jambi City. This condition is influenced by various factors. Objective: This study aims to identify factors associated with stunting among toddlers aged 24–59 months in East Jambi District in 2026. Methods: This study used a quantitative design with a cross-sectional approach. The population was 1,861 toddlers, with a sample of 329 respondents selected using a purposive sampling technique. Data were collected through interviews using a questionnaire and analyzed using the Chi-Square test. Results and discussion: The results of the study showed that there was a relationship between maternal history of KEK (p=0.000; PR=2.718), history of LBW (p=0.018; PR=1.698), early initiation of breastfeeding/IMD (p=0.026; PR=1.662), exclusive breastfeeding (p=0.040; PR=1.591), time of complementary feeding (p=0.005; PR=1.877), immunization status (p=0.012; PR=1.758), and history of diarrhea infection (p=0.000; PR=3.654) with the incidence of stunting in toddlers. Conclusion: There is a significant association between maternal factors, infant feeding practices, health services, and a history of infectious diseases with stunting. Efforts to improve maternal nutrition education, optimize maternal and child health services, and prevent infectious diseases are needed to reduce stunting rates